THE ROLE OF THE RESVERATROL AS ANTIOXIDANT IN IMPROVING THE CHEMICAL AND QUALITATIVE PROPERTIES OF CHILLED GROUND BEEF - Enas Y. R. Alawady,; Alrubeii, A. M. S., (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted to evaluate the effects of resveratrol as a natural antioxidant in improving the chemical properties and some qualitative and microbial properties of chilled ground beef stored at 2 C° for 1, 3, 6, 9, and 12 days. The study included 7 different treatments: T1 (control treatment without addition) T2 (Resveratrol 0.10% g/kg) T3 (Resveratrol 0.20% g/kg) T4 (Resveratrol 0.30% g/kg) T5 (Resveratrol %0.40g/kg) T6 (Resveratrol %0.50g/kg) and T7 (Addition of Butylated hydroxyanisole 0.01% BHA). All addition treatments showed a significant (P